KEPRIBADIAN GURU IDEAL MENURUT PERSPEKTIF AL-GHAZALI DAN RELEVANSINYA DALAM PENDIDIKAN ISLAM KONTEMPORER - nurul akmalunnisa nurul; irfan fauzan nursyabani irfan; Eva Nurfadilla Eva; Mursidin Mursidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Contemporary Islamic education faces a crisis in teacher personality characterized by moral degradation, weak role models, and a materialistic orientation in carrying out the teaching profession. This study aims to analyze the concept of the ideal teacher personality according to Imam Al-Ghazali and its relevance to the challenges of 21st-century Islamic education. Using a qualitative approach with a library research type, the primary data sources of this study are the books Ihya' Ulumuddin, Ayyuha al-Walad, and Bidayat al-Hidayah, while secondary sources are articles from the period 2015-2025. The data analysis technique uses content analysis with a descriptive-interpretive approach. The results of the study indicate that Al-Ghazali's concept of the ideal teacher personality includes three main dimensions: first, the spiritual dimension internalized in the traits of asceticism, sincerity, and piety; second, the moral dimension manifested in exemplary behavior, humility, and compassion; third, the intellectual dimension reflected in mastery of knowledge, scientific honesty, and the harmony between knowledge and deeds. This study found that Al-Ghazali's concept has significant relevance to the four teacher competencies required in contemporary education, but requires contextualization in the aspects of digital literacy, reflective pedagogy, and ongoing professionalism.